2022
DOI: 10.1152/ajpheart.00520.2022
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on cardiac autonomic function in healthy young adults: potential role of symptomatology and time since diagnosis

Abstract: Emerging evidence suggests COVID-19 may affect cardiac autonomic function; however, the limited findings in young adults with COVID-19 have been equivocal. Notably, symptomology and time since diagnosis appear to influence vascular health following COVID-19, but this has not been explored in the context of cardiac autonomic regulation. Therefore, we hypothesized that young adults who had persistent symptoms following COVID-19 would have lower heart rate variability (HRV) and cardiac baroreflex sensitivity (BRS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…However, these previous reports found some conflicting differences in the HRV indices reflective of parasympathetic tone. Stute and colleagues reported an increase in parasympathetic tone while the most recent report by Skow and colleagues showed that HRV indices were unchanged compared to otherwise healthy individuals without a COVID-19 diagnosis and the parasympathetic and global variability improved in the time since the diagnosis ( Stute et al, 2021 ; Skow et al, 2022 ). Consistent with the latter, in the present study, there were no appreciable differences in resting parasympathetic tone, assessed via HRV indices (e.g., RMSSD and HF power).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these previous reports found some conflicting differences in the HRV indices reflective of parasympathetic tone. Stute and colleagues reported an increase in parasympathetic tone while the most recent report by Skow and colleagues showed that HRV indices were unchanged compared to otherwise healthy individuals without a COVID-19 diagnosis and the parasympathetic and global variability improved in the time since the diagnosis ( Stute et al, 2021 ; Skow et al, 2022 ). Consistent with the latter, in the present study, there were no appreciable differences in resting parasympathetic tone, assessed via HRV indices (e.g., RMSSD and HF power).…”
Section: Discussionmentioning
confidence: 99%
“…However, during viral infections, increased circulating inflammatory cytokines are believed to drive this increase in sympathetic nerve activity, while the vagus nerve acts as a neuro-immuno-modulator pathway between the brain and peripheral inflammation. The indices of HRV have been used to assess sympathetic and parasympathetic function in young adults during the weeks following a SARS-CoV-2 infection ( Stute et al, 2021 ; Freire et al, 2022 ; Skow et al, 2022 ). However, these previous reports found some conflicting differences in the HRV indices reflective of parasympathetic tone.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the patients with PCC, baroreflex failure was not correlated with fatigue in contrast to the ME/CFS patients. It should be noted that there are conflicting data on the presence of baroreflex failure in PCC in the literature [ 31 ]. The negative correlation of BRSup with age in the HCs (but not in the ME/CFS patients where it was correlated with the severity of fatigue) provides more evidence for the hypothesis of the accelerated aging of the autonomic nervous system in ME/CFS.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the magnitude of RMSSD enhanced by aHRSR enhanced BRS, suggesting that it may be involved in BP in the short‐ and long‐term. Based on this, it is suggested that stimulation of aHRSR both improves the stability and homeostasis of the autonomic nervous system, and induces changes in the human body through additional physiological stimulation (Savabi et al, 2020 ; Skow et al, 2022 ; Swenne, 2013 ). This shows various possibilities for application, such as healthcare methods and biofeedback methods that individuals can use (Kim et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%